Concepts of Behavioral Accounting From Psychological, Social, and Human Behavior Aspects - Sri Trisnaningsih; Gempita Asmaul Husna (Journal Research of Social Science, Economics, and Management, 2022)
Behavioral accounting connects human behavior and accounting. Behavioral science is part of social science, while behavioral accounting is part of accounting science and behavioral knowledge. But behavioral accounting and behavioral science both use the principles of psychology and sociology to assess and solve a problem. This study aims to determine the concepts that exist in the area of psychology and social psychology and to find out how these are applied to the theoretical system of behavioral accounting. The method used in this research is descriptive which describes how the concepts are applied to the theoretical system in behavioral accounting. The result of this research is that we are able to understand aspects of psychology and social psychology comprehensively. In this study, the main concepts contained in it are explained, where attitudes, changes in attitudes, motivation, perceptions, learning, personality, and emotions are discussed. Then we see how this system is applied theoretically to behavioral accounting.